Modified Qing’e Formula protects against UV-induced skin oxidative damage via the activation of Nrf2/ARE defensive pathway - Zhu, Shan; Qin, Wenxiao; Liu, Tao; Liu, Tao; Ma, Hongfei; Hu, Cunyu; Yue, Xiaofeng; Yan, Yiqi; Lv, Yingshuang; Wang, Zijing; Zhao, Zhiyue; Wang, Xiang; et al. (Frontiers in Pharmacology, 2022)
Exposure to ultraviolet (UV) light triggers the rapid generation and accumulation of reactive oxygen species (ROS) in skin cells, which increases oxidative stress damage and leads to photoaging. Nuclear factor E2-related factor 2 (Nrf2) modulates the antioxidant defense of skin cells against environmental factors, especially ultraviolet radiation. Natural products that target Nrf2-regulated antioxidant reactions are promising candidates for anti-photoaging. The aim of this study was to investigate the protective effect of Modified Qing’e Formula (MQEF) on UV-induced skin oxidative damage and its molecular mechanisms. In this study, the photoaging models of human keratinocytes (HaCaT) and ICR mice were established by UV irradiation. In vitro models showed that MQEF displayed potent antioxidant activity, significantly increased cell viability and reduced apoptosis and excess ROS levels. Meanwhile, the knockdown of Nrf2 reversed the antioxidant and anti-apoptotic effects of MQEF. In vivo experiments indicated that MQEF could protect the skin against UV-exposed injury which manifested by water loss, sensitivity, tanning, wrinkling, and breakage of collagen and elastic fibers. The application of MQEF effectively increased the activity of antioxidant enzymes and reduced the content of malondialdehyde (MDA) in mice. In addition, MQEF was able to activate Nrf2 nuclear translocation in mouse skin tissue. In summary, MQEF may attenuate UV-induced photoaging by upregulating Nrf2 expression and enhancing antioxidant damage capacity. MQEF may be a potential candidate to prevent UV-induced photoaging by restoring redox homeostasis.